Subspace Projection-Based Collision Detection for Physical Interaction Tasks of Collaborative Robots - Lee, Sang-Duck; Ahn, Kuk-Hyun; Song, Jae-Bok (International journal of precision engineering and manufacturing, 2019)
In recent years, various collision detection methods have been proposed for safe human–robot collaboration; these methods are usually model-based. However, most tasks conducted by collaborative robots involve a physical robot–environment interaction, and it is very difficult to design a model of such interaction that varies depending on the external environment. Therefore, this study proposes a method for detecting collision between a human and a robot while the robot executes a task involving physical interaction with an unknown environment. To this end, a collision detection index is suggested based on the subspace projection technique. The proposed collision detection scheme is verified experimentally using a 7-DOF robot arm, and the experimental results show that collisions can be detected reliably by the proposed method.